POLITIK MEDIA MENGKONSTRUKSI BERITA (Analisis Wacana Berita: âKomnas HAM Pantau Kasus Penembakanâ Harian Radar Lampung, Minggu 20 Nopember 2011) - Suharti, Bangun (JURNAL SOSIOLOGI, 2014)
This study uses discourse analysis of Norman Fairclough models. This model does not only analyze the text, but also the context. Context will further analyze how ideology, history, hegemony, and the political economy of media, news affecting construction of the news text. Action / effect analyzes what is desired by the media, in constructing an event in the news.This study proves that knowledge, the proximity of the reporter to the event, ideology, hegemony vested interests of advertisers, media cultural institutions, as well as the political economy of the media plays a major role in the process of news construction . Constructed news will further affects the public perception of the event, as well as those who become participating in the news (involved).